Laboratory manual in fish biology / Malcolm Jobling - Jobling, Malcolm (Nicaragua: Norwegian College of Fishery Science, 1998)
Facts about fishes, animal classification and the, major groups of fishes, what is a fish, the cartilaginous fishes elasmobranshiomorphi, diversity in fish form and function, the naming and identification of fishes; the laboratory exercise, the laboratory course programme, chonbrichthyes the extant cartilaginous fishes, examination of the internal organs, body form and life styles of the cartilaginous fishes.
Contents, ilustrado, tabla, grafica
Col. Pesc
Keywords: 1. LABORATORIOS 2. FISH BIOLOGY 3. GENETICA 4. PESCA